Strength training and changes in the dynamics of running economy - Cacek, M.; Tomas, K.; Martin, D. (Journal of Human Sport & Exercise, 2014)
The aim of this study was to examine an acute effect of 4RM training and plyometric training (PT) on running economy (RE; O2 consumption) in endurance runners during a 48 hour interval. Eight performance runners (age 25.4±1.4 years) completed a maximum strength training (4RM) of lower limbs (3 sets, rest 2 min, 5 exercises) and subsequently underwent a RE test on a treadmill (speed 8, 10 and 12 km/h) at three time intervals (0, +24 and +48 h) after the training. We found that the average VO2/BMmin and DeltaVO2/BM·min at the given speed increased from baseline (a pretest 48 h before the strength intervention) by 2.3-5.6% and culminated after 24 h. These changes in RE after the strength intervention were not statistically significant, when compared to the pretest (48 h before the intervention). The second investigation was conducted in seven runners (age 25±1.6 years). This time the intervention was plyometric (7 sec load, rest 2 min, maximum intensity, 3 sets, 6 exercises on the dominant lower limb). We found that the average VO2/BM·min and DeltaVO2/BM·min at given speeds at intervals 0, +24 and +48 h did not increase, when compared to the pretest (p < 0.05; max +1%). These minimal changes probably resulted from the design of the PT, which had not a sufficiently destructive effect on muscle cells. The comparison of these two investigations indicates a stronger (although statistically insignificant) deterioration of RE after 4RM training versus PT.